A new species of Aplectana Railliet & Henry (Nematoda: Cosmocercidae) in Amphisbaena alba Linnaeus (Squamata: Amphisbaenidae) from Minas Gerais State, Brazil - Vieira, Fabiano Matos; Gonçalves, Paula Araujo; Lima, Sueli De Souza; de Sousa, Bernadete Maria; Muniz-Pereira, Luís Cláudio (Zootaxa, 2020)
In the present study, we described and illustrated Aplectana minaensis n. sp. (Ascaridida: Cosmocercidae) from the intestinal caecum of Amphisbaena alba Linnaeus (Squamata: Amphisbaenidae). Aplectana minaensis n. sp. is the 5th species described in Brazilian hosts and 58th species assigned to the genus. This species differs from its congeners by a set of unique characters in males: the presence of one unpaired precloacal papilla and gubernaculum, the papillae pattern (4+1:2:6) and total number (12+1), and the size of spicules (400–605 µm). Among the Aplectana species with an unpaired precloacal papilla and gubernaculum, only A. minaensis n. sp. and A. nebulosa Gomez, González & Sanabria, has less than 20 pairs of caudal papillae. However, these species differ in the number of caudal papillae in males (12+1 vs. 13–14+1, respectively); the number and arrangement of post cloacal papillae (6 pairs: 1st to 4th pairs ventral, 5th pair laterodorsal, 6th pairventral vs. five pairs: 1st and 2nd ventral, 3rd lateral, 4th ventral, 5th lateral); and by the size of spicules (413–600 vs. 85–126 µm).